Efficacy of Intravitreal Triamcinolone Acetonide in Diabetic Macular Edema - Tahira Afzal Khan, Taiba Baig (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetic macular edema (ME) can be treated by intravitreal injection of Triamcinolone acetonide (TA). The scope of the study was to determine its efficacy in our setup in order to develop our local guidelines for its routine use in our setup. Objective: To determine the effect of intravitreal Triamcinolone(TA) for the management of diabetic macular edema(ME) Material and Methods: This descriptive case series carried out at Al-Shifa Trust Eye Hospital, Rawalpindi in 2019. Total 149 patients cases of either gender aged 40-75 years with history of DM of >10 years, VA<6/36 assessed by Snellen VA chart and who had clinically significant ME as assessed by indirect ophthalmoscopy were included in the study. 4mg/0.1 ml of TA was injected through pars plana under local anesthesia. Efficacy was determined at six week post treatment. Results: Treatment was found to be effective in overall 40.9%(n=61) cases, 44.7%(n=38) males, 35.9%(n=23) were females, 35.1%(n=20) were between 41-50 years age, 42.9%(n=30) between 51-60 years, 50%(n=11) had >60 years, 44.5%(n=49) at baseline VA of 6/36 and 30.8%(n=12) with baseline VA of 6/60 showed improvement in VA. Conclusion: Administration of triamcinolone acetonide(TA) intravitreal inj. is an effective modality for the treatment for diabetic macular edoema, and this treatment may lead to an improvement in visual acuity